Rancang Bangun Sistem Pemantauan Suhu Kowi pada Peleburan Emas Berbasis IoT Menggunakan ESP32 dan Blynk - Sujono Sujono; Mohammad Ghazi Al Ghifari (JOURNAL SAINS STUDENT RESEARCH, 2026)
The gold jewelry industry, particularly within Small and Medium Enterprises (SMEs), often faces crucial challenges regarding product quality consistency due to high reliance on conventional melting methods. Currently, the vital control of melting temperature relies solely on the operator's visual intuition in observing the glowing color gradation of the crucible. Dependence on this subjective approach carries significant production risks, including porosity defects, low metal alloy homogeneity, and substantial financial losses due to gold mass shrinkage or evaporation caused by overheating. This study aims to engineer a precise real-time temperature monitoring system based on the Internet of Things (IoT) to address these issues. The system is developed by integrating an ESP32 microcontroller as the main processing unit that processes digital data from a Type-K thermocouple sensor and MAX6675 amplifier module, then visualizing the data directly through the Blynk app interface on a smartphone. The research method includes designing hardware resistant to extreme heat environments, developing smart notification algorithms for early warning, and field testing on 24-karat pure gold melting. Test results show that the system is capable of monitoring the thermal characteristics of melting through outer crucible wall measurements up to a stable temperature of 625 degrees Celsius, which empirically correlates with the liquid phase of pure gold. The system also features responsive data transmission performance with an average latency of only 1.2 seconds. Additionally, the early warning feature successfully operates effectively at a calibration threshold of 620 degrees Celsius. Implementation of this system proves capable of increasing operational time efficiency and minimizing the risk of melting failure, making it a vital appropriate technology solution for the modernization of the gold industry.